1977
DOI: 10.1172/jci108831
|View full text |Cite
|
Sign up to set email alerts
|

Nephrogenous Cyclic Adenosine Monophosphate as a Parathyroid Function Test

Abstract: A B S T R A C T Nephrogenous cyclic AMP (NcAMP), total cyclic AMP excretion (UcAMP), and plasma immunoreactive parathyroid hormone (iPTH), determined with a multivalent antiserum, were prospectively measured in 55 control subjects, 57 patients with primary hyperparathyroidism (10 HPT), and 10 patients with chronic hypoparathyroidism.In the group with 1°HPT, NcAMP was elevated in 52 patients (91%), and similar elevations were noted in subgroups of 26 patients with mild (serum calcium c 10.7 mg/dl) or intermitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
112
0
10

Year Published

1979
1979
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(135 citation statements)
references
References 45 publications
13
112
0
10
Order By: Relevance
“…An increase in adenylate cyclase activity and accumulation of intracellular cAMP after PTH administration have been demonstrated (16,26). The intracellular accumulation of cAMP and subsequent leakage from the renal tubular cells is considered to be an explanation for the increase in urinary excretion of CAMP, and thus, the latter change has been used as an indicator of the renal responsiveness to PTH (3,8,22,32). Our study confirms the earlier reports of a phosphaturic response to CT in both humans (1, 2, 7, 19) and rats (24).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…An increase in adenylate cyclase activity and accumulation of intracellular cAMP after PTH administration have been demonstrated (16,26). The intracellular accumulation of cAMP and subsequent leakage from the renal tubular cells is considered to be an explanation for the increase in urinary excretion of CAMP, and thus, the latter change has been used as an indicator of the renal responsiveness to PTH (3,8,22,32). Our study confirms the earlier reports of a phosphaturic response to CT in both humans (1, 2, 7, 19) and rats (24).…”
Section: Resultssupporting
confidence: 88%
“…Studies have shown increased renal formation and urinary excretion of cAMP in response to PTH (1 I, 12). This change in the urinary excretion of cAMP is considered a qualitative indicator of the effect of PTH on the kidney (8,22,32). Some studies also have shown an increase in the formation of cAMP in the kidney after CT administration (20,27).…”
Section: Speculationmentioning
confidence: 99%
“…We determined NcAMP as an index ofthe biological activity of PTH on the kidney (21,22). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Calcium, phosphorus, magnesium, and electrolytes in serum and PTH in plasma were determined in samples obtained after overnight fast. cAMP was analyzed by radioimmunoassay in at least four sequential 12-h urine collections and adjusted for glomerular filtration rate as follows (17): (UCAMP X SCr)/U,r, where UC,AMP is the urinary concentration of cAMP, and Scr and U,. are serum and urine concentrations of creatinine, respectively.…”
Section: Study Protocolmentioning
confidence: 99%